Pengaruh Organisasi Pembelajaran, Pemberdayaan Karyawan, dan Kepuasan Kerja Terhadap Kinerja Karyawan Industri Manufaktur Otomotif di Jakarta - Indi Wianti; Samudro Seto (Economic Reviews Journal, 2026)
The automotive manufacturing industry sector is one of the drivers of the national economy in the manufacturing sector; however, labor productivity in Indonesia still lags behind other Southeast Asian countries. Challenges such as low discipline and communication barriers make it imperative for companies to optimize employee performance. This study aims to analyze the effect of a learning organization, employee empowerment, and job satisfaction on employee performance in the manufacturing industry in Jakarta. This study uses a quantitative approach with a survey method. Data were collected through online questionnaires using a five-point Likert scale from 140 respondents selected through purposive sampling with the criteria of permanent employees who have worked for at least one year. Data analysis was conducted using multiple linear regression through IBM SPSS software after meeting classical assumption tests. The results of the study indicate that Simultaneously, organizational learning, employee empowerment, and job satisfaction have a positive and significant effect on employee performance. Partially, these three variables are proven to have a positive and significant impact. These findings confirm that a continuous learning culture, proper delegation of authority, and collective fulfillment of employee welfare can enhance work effectiveness and the quality of production outcomes in the manufacturing sector.